Turning strategic network resources into performance : The mediating role of network identity of small- and medium-sized enterprises - Partanen, Jukka; Kauppila, Olli-Pekka; Sepulveda, Fabian; Gabrielsson, Mika (Wiley, 2018)
Research Summary: This article examines the relationship between strategic network resources; the network identity (i.e., the self‐perceived attractiveness as a partner based on the firm's existing and prior relationships); and firm performance among established small‐ and medium‐sized enterprises (SMEs). We test our hypotheses within the sample of 199 internationalized SMEs in Finland. We contribute to the discussion on the performance effects of network resources among small firms by demonstrating that: (a) networks can become a source of strategic resources for SMEs, which enhance firm performance; and (b) such concrete strategic resource exchange builds evidence‐based identity, which helps entice and convince customers and other partners to invest in the collaboration so that strategic resources can be transferred to sustain firm performance beyond the early stages. Managerial Summary: The purpose of this article is to investigate how an SME's strategic collaboration and its attractiveness as a partner enhance firm performance. The key message for practitioners is twofold. First, the conventional view suggests that strategic resources should be kept in‐house and that too much dependency on partners may lead to a vulnerable power position. Yet, we demonstrate that SMEs can also enhance their performance by acquiring strategic resources from their partners. Second, while weak affiliations with prestigious partners may help build credibility in the early stages of firm development, it is the strategic collaboration and concrete resource exchange that seem to attract other customers and business partners to commit to, and invest in, the collaboration which, in turn, enhances performance beyond the early stages.
Keywords: network identity; network resources; performance; reputation; small and medium-sized firms; fi=Johtaminen ja organisaatiot|en=Management and Organization|